PTU-052 Liver fibrosis in patients on long-term methotrexate therapy: correlation of serological markers and transient elastography. (23rd September 2015) - Barnova, I; Bray, A; Shetty, S; Kennedy, C; Gordon, F; Przemioslo, R
Abstract : Introduction: Long-term use of Methotrexate (MTX) therapy carries a risk of hepatic fibrosis. Liver biopsy is the gold standard in assessing hepatic fibrosis in patients treated with MTX. Procollagen lll aminopeptide (P3NP) assessment can reduce the number of liver biopsies but has a poor predictive value. Transient elastography (TE) is an indirect assessment of liver fibrosis using liver stiffness indices. The positive predictive value (PPV) of TE for F1/F0 disease is 0.95, for F2/F3 is 0.88 and F4 is 0.95 compared to liver biopsy and P3NP is a comparison to these findings. We studied patients taking long-term MTX and compared liver fibrosis indices using P3NP and TE. Methods: Patients taking long-term MTX therapy were recruited from two centres. Participants were divided into three groups: Dermatology, Rheumatology and IBD. All patients had TE and P3NP levels taken at the same time. The results of TE and P3NP levels were compared. Results: We collected samples from 79 patients: 24 Dermatology, 42 Rheumatology and 13 IBD patients. The results are shown in Abstract 052, the correlation was best achieved in patients with IBD (r=0.92). The dermatology and rheumatology group showed very similar values of correlation in spite of the fact that the average cumulative dose of dermatology patients was almost doubled. The correlation coefficient of P3NP and TE was 0.667 in dermatology patients and 0.62 in rheumatology patients. Conclusion: The correlation coefficient of P3NP and TE readings was 0.71 in all patients. The best correlation was in patients with IBD. It is likely that P3NP levels are not a satisfactory standard to compare to and liver biopsy comparison would be more robust. In all cases more abnormal high P3NP values were obtained compared to TE in patients who had no clinical and radiological evidence of high-grade fibrosis. These data suggest a better correlation between TE and liver fibrosis stage. Second, there was no significant difference in liver fibrosis results between dermatology and rheumatology group of patients.